My two blankets - Kobald, Irena; Blackwood, Freya (Boston : Houghton Mifflin Harcourt, 2014)
Cartwheel has arrived in a new country, and feels the loss of all she's ever known. She creates a safe place for herself under an "old blanket" made out of memories and thoughts of home. But when she meets a new friend, the relationship helps her take her first steps into a new culture, and Cartwheel begins to weave a "new blanket," one of friendship and a renewed sense of belonging.
Originally published in Australia in 2014 by Little Hare Books.
Keywords: Immigrants -- Juvenile fiction; Belonging (Social psychology) -- Juvenile fiction; Homesickness -- Juvenile fiction; Immigrants -- Fiction; Belonging (Social psychology) -- Fiction; Homesickness -- Fiction; Picture books; Fiction